Light‐Triggered Green Fluorescent Protein Silencing in Human Keratinocytes in Culture Using Antisense Oligonucleotides Coupled to a Photoreactive Ruthenium(II) Complex. Issue 11 (8th August 2014) - Marcélis, Lionel; Van Overstraeten‐Schlögel, Nancy; Lambermont, Javiera; Bontems, Sébastien; Spinelli, Nicolas; Defrancq, Eric; Moucheron, Cécile; Kirsch‐De Mesmaeker, Andrée; Raes, Martine
Abstract A photoreactive ruthenium(II) complex that contains two tetraazaphenanthrene (TAP) and one phenanthroline (phen) ligands was synthesized and then tethered to (antisense) oligonucleotides (Ru–ASO) to target a destabilized GFP (dGFP). The specificity of the photoreaction of this Ru–ASO conjugate was studied in vitro by polyacrylamide gel electrophoresis (PAGE) experiments in denaturing conditions. Other nonspecific Ru–ASO conjugates were also prepared and evaluated with human keratinocytes that expressed dGFP. An illumination‐dependent cytotoxicity was observed for most Ru–ASO conjugates that varied from 10 to almost 40 %, but only the specific Ru–ASO conjugate was able to significantly reduce GFP expression in illuminated cells.